The The Prototype of An Automated Temperature Control System for Broiler Chicken Coops Based on Arduino and The Internet of Things (IoT) - Wiguna, Didik; Huda, Didik Nur (Journal Global Technology Computer, 2025)
This study aims to design and implement an Internet of Things (IoT)–based automated temperature control prototype for broiler chicken housing using an Arduino Uno and ESP32 microcontroller architecture. The proposed system integrates a DHT22 temperature–humidity sensor, relay modules, a cooling fan, and a heating lamp to regulate the coop microclimate based on predefined temperature thresholds. The Arduino Uno functions as the primary data acquisition and control unit, reading environmental parameters and executing actuator control logic, while the ESP32 handles wireless communication by transmitting sensor data to a MySQL database via WiFi at a configurable interval of 5 seconds. A simple yet effective control algorithm is applied, in which the fan is activated when the temperature exceeds 30.8 °C, while the heating lamp operates based on a scheduled brooding cycle. Experimental results demonstrate that the system is capable of reading temperature data in real time, responding appropriately to environmental changes, and reliably storing data in the database. The main contribution of this research lies in the development of a low-cost, dual-microcontroller IoT prototype that combines real-time monitoring, automatic temperature control, and flexible data logging, making it suitable for small to medium scale broiler farming applications and serving as a foundation for future enhancements involving humidity-based control.